Implementation of Article 2, Article 3 Decree of the State Minister of Agraria / Chairman of National Land Agency number 16 year 1997 on the decrease of land ownership rights to be changed to building use rights through the bidding process: Study at the Blitar Regency Land Office - Gunawan Hariyanto,; Suhariningsih,; Bambang Winarno,; Sihabuddin, (Technium Social Sciences Journal, 2020)
However, if at the time of the auction the guarantee is won by an entity, in this case a legal entity, then the status of ownership of the land rights must be immediately changed from property rights to building use rights. This is based on a decree, namely the Decree of the State Minister for Agrarian Affairs / Head of the National Land Agency Number 16 of 1997 contained in article 2 paragraph 3, which includes the following contents : In the case of a land right, in this case a property right a body is requested for several changes to it’s rights, in this case a legal entity obtaining the rights through an auction process, then the rights must be transferred immediately and then registered from property rights to building use rights. In it’s implementation, it’s due to the fact that at the time the status of ownership of land rights, in this case ownership rights, is then converted into rights to build by an individual to an entity, which in this case the legal entity requires a lot of costs, and with a significant amount of time. Not for a moment, then it can create a new problem or problem that must be resolved immediately. The method used in this research is sociological juridical which is carried out by direct interviews with sources who are closely related to the research. Based on the results of the research, the solution is as follows: First, the application of the reduction of property rights to be converted into building uses based on Article 2 Agrarian/Head of the National Land Agency in 1997, namely: in it’s implementation, because at the time the status of ownership rights to land, which in this case is a right of ownership, is then converted into a right to build by an individual to an entity, which in this case the legal entity requires a lot of costs, and with a long time, it can create a problem or new constraints that must be immediately resolved. Second, namely the obstacles in the Status of Ownership of Freehold Land to Rights of Land through the Tender Process Based on the Decree of the Minister/Head of the National Land Agency, are as follows: Lack of transparency in and information on land tenure and ownership; Land titling cannot be done quickly; Limited skilled personnel; The demands for juridical technical accuracy of the documents on which land rights are based must be relatively accurate; Incomplete Standard to date; Until now, there is no unified definition of customary land and state land.